Non invasive prenatal diagnosis of ?- Thalassemia, A narrative review study (Bangladesh Journal of Medical Science, 2017)
?- Thalassemia is major monogenic disorder. A practical way to prevention of Thalassemia is identification of carries couples; genetic counseling and offer prenatal diagnose services for both carrier couples. Routine prenatal diagnose are chorionic villus sampling and amniocentesis, but both of them are invasive method and they can be ended to bleeding and pregnancy loss. Recently non invasive prenatal diagnosis has been done by researchers for early detection of pre-eclampsia, chromosomal aneuploidies, RhD-genotyping. Regarding non invasive prenatal diagnosis of ?- Thalassemia, detection of paternally inherited mutation in maternal plasma is possible. If the fetus inherited normal paternal allele the performance of invasive method it is not necessary, so this method can be eliminate 50% performance of routine prenatal diagnosis.Bangladesh Journal of Medical Science Vol.16(2) 2017 p.196-202